Preclinical Evaluation and Advancements in Vascularized Bone Tissue Engineering - Toshiyuki Kawai (Biomimetics)
Large segmental bone defects present significant challenges due to the insufficient vascularization of implanted grafts, necessitating advances in vascularized bone tissue engineering. Recent innovations focus primarily on enhancing graft vascularization through advanced biomaterial scaffolds, precise three-dimensional (3D) bioprinting technologies, biochemical interventions, and co-culture techniques. Biomaterial scaffolds featuring microchannels and high-surface-area architectures facilitate endothelial cell infiltration and subsequent vessel formation. Concurrently, sophisticated 3D-bioprinting methods, including inkjet, extrusion, and laser-assisted approaches, enable the precise placement of endothelial and osteogenic cells, promoting anatomically accurate vascular networks. Biochemical strategies that utilize the simultaneous delivery of angiogenic factors (e.g., vascular endothelial growth factor) and osteogenic factors (e.g., bone morphogenetic protein-2) effectively couple angiogenesis and osteogenesis. Additionally, co-culturing mesenchymal stem cells and endothelial progenitors accelerates the development of functional capillary networks. Preclinical studies consistently demonstrate superior outcomes for prevascularized grafts, as evidenced by enhanced vascular inosculation, increased bone formation, and improved mechanical stability compared to non-vascularized controls. These technological advancements collectively represent significant progress toward the clinical translation of engineered vascularized bone grafts capable of addressing complex and previously intractable bone defects.